2018
DOI: 10.7150/ijms.25140
|View full text |Cite
|
Sign up to set email alerts
|

Iroquois Homeodomain transcription factors in ventricular conduction system and arrhythmia

Abstract: Iroquois homeobox genes, Irx, encode cardiac transcription factors, Irx1-6 in most mammals. These six transcription factors are expressed in different patterns mainly in the ventricular part of the heart. Existing researches show that Irx genes play key roles in the differentiation and development of ventricular conduction system and the establishment and maintenance of gradient expression of potassium channels, Kv4.2. Our main focus of this review is on the recent advances in the discovery of above-mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…Among the strongest downregulated genes ( Figure 2D) are several major urinary proteins (Mups), also known as α 2 µ-globulins, such as Mup19, Mup21, Mup15, Mup17, Mup-ps16, Mup-ps14 and Mup12. Expression of Mup proteins is known to be induced by androgens and they are physiologically relevant, because they bind small hydrophobic molecules, such as steroid hormones, lipids and retinoids in plasma [40]; several cytochrome P450 enzymes; the sushi domain-containing protein 4 (SUSD4) which inhibits complement factors [41]; calpains (e.g., capn11, Capn8) that act as calcium-dependent cysteine proteases, fatty acid elongase 3 (Elovl3); and roquois homeobox protein 1 (lrx1-6) that is known as a cardiac transcription factor [42]. The role of many of these differential genes in liver fibrosis remains unknown.…”
Section: Rna-seq Demonstrates Downregulation Of Pericentral and Upregmentioning
confidence: 99%
“…Among the strongest downregulated genes ( Figure 2D) are several major urinary proteins (Mups), also known as α 2 µ-globulins, such as Mup19, Mup21, Mup15, Mup17, Mup-ps16, Mup-ps14 and Mup12. Expression of Mup proteins is known to be induced by androgens and they are physiologically relevant, because they bind small hydrophobic molecules, such as steroid hormones, lipids and retinoids in plasma [40]; several cytochrome P450 enzymes; the sushi domain-containing protein 4 (SUSD4) which inhibits complement factors [41]; calpains (e.g., capn11, Capn8) that act as calcium-dependent cysteine proteases, fatty acid elongase 3 (Elovl3); and roquois homeobox protein 1 (lrx1-6) that is known as a cardiac transcription factor [42]. The role of many of these differential genes in liver fibrosis remains unknown.…”
Section: Rna-seq Demonstrates Downregulation Of Pericentral and Upregmentioning
confidence: 99%
“…In drosophila, the Iroquois gene (IRO) encodes a prepattern gene that controls the formation of bristles on the thorax [7]. In human, the Iroquois homeobox (IRX) family consists of six members (IRX1-IRX6) that contain a homeobox and a so called IRO box [8]. The IRX gene are transcription factors that play key roles in differentiation and development [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The IRX gene are transcription factors that play key roles in differentiation and development [9,10]. These six IRX genes are organized into two clusters of three, each are located on cytoband 5p15.33 (IRX1, IRX2, and IRX4) and on cytoband 16q12.2 (IRX3, IRX5, and IRX6) [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…IRX2 was shown to participate in cerebellum formation and potentially the ventricular conduction system (VCS) [ 89 , 90 ], while IRX3 was shown to have a definitive role in establishing fast conduction in the VCS [ 90 ]. The downregulation of IRX2 and 3 in endothelial cell lineage suggested that these factors may have an inhibitory role in processes related to endothelial-specific function.…”
Section: Resultsmentioning
confidence: 99%